Dynamic strength development of lower limbs in basketball - Betak, B. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2011)
An author`s aim is to contribute by enhancing some knowledge about the possibilities of dynamic strength development of lower limbs at a junior basketball team of ŠKP Banska Bystrica (Police sport club Banska Bystrica). Another point is that the main aim of this research was to analyze available data of bibliographical roots. Realization of measurements entrance of dynamic strength belonged to the major tasks by the help of some motoric tests. Furthermore, to set up a kinetic programme of the development of dynamic strength and to realize its exit measurements belonged to the major task as well. Among the main motoric tests belonged a vertical jump, standing broad jump and triple jump. A research body was created by fourteen juniors of basketball team ŠKP Banska Bystrica who participated on a six-week kinetic programme. In each of the kinetic tests there was compared data pairs (entrance and exit ones). Thus, the compared results have shown the increase or decrease of the dynamic strength level of the lower limbs at junior basketball team ŠKP Banska Bystrica.In conclusion, we can claim from measured results that a kinetic program has helped to the development of dynamic strength.